1993
DOI: 10.1161/01.hyp.21.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypovolemic stress alters autonomic modulation of heart rate.

Abstract: In response to changes in central venous volume, changes in vagal efferent cardiac outflow have been demonstrated in animals but not in humans. In this study, frequency domain analysis was used to quantify modulation of heart rate by respiration and blood pressure in normal human adults undergoing mild central hypovolemic stress induced by blood donation and postural change. In supine subjects, blood donation caused no change in mean heart rate, pulse pressure, or in the variance of heart rate or blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
48
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 38 publications
10
48
1
2
Order By: Relevance
“…First, although the presence of the Bainbridge reflex has been controversial in humans (3), one report has clearly demonstrated reflex tachycardia with volume loading in humans (17). Furthermore, Triedman et al (25) found that mild hypovolemia from a 10% blood donation significantly changed arterial baroreflex control of heart rate without changing either mean heart rate or arterial pressure, consistent with the findings of others during low levels of LBNP (8).…”
supporting
confidence: 82%
“…First, although the presence of the Bainbridge reflex has been controversial in humans (3), one report has clearly demonstrated reflex tachycardia with volume loading in humans (17). Furthermore, Triedman et al (25) found that mild hypovolemia from a 10% blood donation significantly changed arterial baroreflex control of heart rate without changing either mean heart rate or arterial pressure, consistent with the findings of others during low levels of LBNP (8).…”
supporting
confidence: 82%
“…Candidate spectral processing algorithms included Fast Fourier Transform (FFT) with BlackmanTukey estimation (BT) [6], auto regressive (AR) [7][8], and Wavelets processing using Haar and db10 wavelets [10].…”
Section: Methodsmentioning
confidence: 99%
“…HbA1c, hemoglobin A1c; LDL-C, low-density lipoprotein cholesterol; HDL-C, high-density lipoprotein cholesterol. (Triedman et al 1993;Kosowsky et al 2002;Haberthür et al 2003;Zöllei et al 2004). According to the five classes of hemorrhagic shock, the quantity of blood volume loss in the present study constitutes less than a class I hemorrhage (15% of the circulating blood volume) (American College of Surgeons Committee on Trauma 2012).…”
Section: Cardiovascular Dynamics and Autonomic Regulation During Bloomentioning
confidence: 99%
“…The autonomic nervous system, which mediates the baroreceptors (arterial and carotid sinus) and cardiopulmonary receptor, establishes a short-term regulatory system for maintaining cardiovascular stability. This mostly initial compensatory mechanism leads to cardiac vagal withdrawal and sympathetic activation immediately induced by blood volume reduction (Schadt and Ludbrook 1991;Triedman et al 1993;Furlan et al 2001). In our study, with the course of blood volume reduction, the HF component, as an index of cardiac vagal nerve activity, and the LF/HF ratio, as an index of sympathetic nerve activity, signifi cantly continued to decrease and increase from the pre-blood to post-blood donation stage in the HbA1c < 6.5% group.…”
Section: Cardiovascular Dynamics and Autonomic Regulation During Bloomentioning
confidence: 99%
See 1 more Smart Citation